2008
DOI: 10.1182/blood-2007-07-100651
|View full text |Cite
|
Sign up to set email alerts
|

CEP-18770: A novel, orally active proteasome inhibitor with a tumor-selective pharmacologic profile competitive with bortezomib

Abstract: Modulating protein ubiquitination via proteasome inhibition represents a promising target for cancer therapy, because of the higher sensitivity of cancer cells to the cytotoxic effects of proteasome inhibition. Here we show that CEP-18770 is a novel orally-active inhibitor of the chymotrypsin-like activity of the proteasome that down-modulates the nuclear factor-kappaB (NF-kappaB) activity and the expression of several NF-kappaB downstream effectors. CEP-18770 induces apoptotic cell death in multiple myeloma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(225 citation statements)
references
References 42 publications
5
218
0
2
Order By: Relevance
“…The two approved proteasome-inhibiting drugs, bortezomib and carfilzomib, by design target the β5 subunit of the constitutive proteasome and the immunoproteasome, which mediate the rate-limiting proteolytic proteasome activity. 1,12 Several β5-targeted next generation proteasome inhibiting drugs like delanzomib 13 (CEP-18770), ixazomib 14 (MLN-2238), and oprozomib 15 (ONX-0912) are under development. Mutations in the bortezomib binding pocket 16,17 have been suggested to provide bortezomib resistance in myeloma, based on in vitro studies, but have not been confirmed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The two approved proteasome-inhibiting drugs, bortezomib and carfilzomib, by design target the β5 subunit of the constitutive proteasome and the immunoproteasome, which mediate the rate-limiting proteolytic proteasome activity. 1,12 Several β5-targeted next generation proteasome inhibiting drugs like delanzomib 13 (CEP-18770), ixazomib 14 (MLN-2238), and oprozomib 15 (ONX-0912) are under development. Mutations in the bortezomib binding pocket 16,17 have been suggested to provide bortezomib resistance in myeloma, based on in vitro studies, but have not been confirmed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…CEP18770 (Cephalon Inc.): As a reversible boronic acid proteasome inhibitor, CEP18770 caused similar proteasome and apoptotic profi les in multiple myeloma xenograft models following intravenous or oral administration (Piva, 2008;Marblestone, 2009). CEP-18770 also induces synergistic inhibition of multiple myeloma cell viability with combination with melphalan or bortezomib.…”
Section: Mln9708 (Millennium Pharmaceuticals Inc)mentioning
confidence: 99%
“…Proteasome inhibitors have also been identified from plant extracts. This is the case for celastrol from the Chinese medicinal orally-active inhibitor of the chymotrypsin-like activity [64,65]. These proteasome inhibitors are primarily designed as anticancer agents but they can be of interest for other pathologies characterized by alterations in the proteasome proteolytic pathway including autoimmune and inflammatory diseases, myocardial infarction, and ischemic brain injury [66].…”
Section: Natural Product-biological Target: a Pas De Deux In Drug Dismentioning
confidence: 99%